Determination and correlation of pyridoxine hydrochloride solubility in different binary mixtures at temperatures from (278.15 to 313.15) K. (March 2016) - Han, Dandan; Li, Xiaona; Wang, Haisheng; Wang, Yan; Du, Shichao; Yu, Bo; Liu, Yumin; Xu, Shijie; Gong, Junbo
Highlights: Solubility of pyridoxine hydrochloride in three binary mixtures was determined. Experimental solubility of pyridoxine hydrochloride was correlated by four models. Mixing thermodynamics of pyridoxine hydrochloride were calculated and discussed. Abstract: The solubility of pyridoxine hydrochloride in binary solvent mixtures, including (acetone + water), (methanol + water) and (ethanol + water), was measured over temperature range from (278.15 to 313.15) K by a gravimetric method at atmospheric pressure ( P =  0.1 MPa). The solubility increased with increasing temperature in binary solvent mixtures at constant solvent composition. Besides, the dissolving capacity of pyridoxine hydrochloride in the three binary solvent mixtures at constant temperature ranked as (methanol + water > ethanol + water > acetone + water) in general, partly depending on the polarity of the solvents. Additionally, the modified Apelblat equation, van't Hoff equation, CNIBS/R–K model and Jouyban–Acree model were used to correlate the solubility data in binary mixtures, it turned out that all the selected thermodynamic models could give satisfactory results. Furthermore, the mixing thermodynamic properties of pyridoxine hydrochloride in different binary solvent mixtures were also calculated and discussed. The results indicate that the mixing process of pyridoxine hydrochloride in the selected solvents is exothermic.